Genetic Responses to Nanostructured Calcium-phosphate-coated Implants - Jimbo, R.; Xue, Y.; Hayashi, M.; Schwartz-Filho, H. O. [UNESP]; Andersson, M.; Mustafa, K.; Wennerberg, A. (Sage Publications Inc, 2011)
Nanostructured calcium phosphate (CaP) has been histologically and biomechanically proven to enhance osseointegration of implants; however, conventional techniques were not sufficiently sensitive to capture its biological effects fully. Here, we compared the conventional removal torque (RTQ) evaluation and gene expression in tissues around nanostructured CaP-coated implants, using real-time RT-PCR, with those of uncoated implants, in a rabbit model. At 2 wks, RTQ values were significantly higher, alkaline phosphatase (ALP) expression was significantly higher, and runt-related transcription factor 2 and tumor necrosis factor-alpha expressions were significantly lower in the coated than in the uncoated implants. This indicates that inflammatory responses were suppressed and osteoprogenitor activity increased around the CaP-coated surface. At 4 wks, although RTQ values did not significantly differ between the 2 groups, ALP and osteocalcin (OCN) were significantly up-regulated in the coated group, indicating progressive mineralization of the bone around the implant. Moreover, an osteoclast marker, adenosine triphosphatase, which indicates acidification of the resorption lacunae, was significantly higher for the coated implants, suggesting gradual resorption of the CaP coating. This study reveals detailed genetic responses to nanostructured CaP-coated implants and provides evidence that the effect of nanotopography is significant during the osseointegration cascade.
Keywords: gene expression; biomaterials; nanotopography; bone implant interactions; osseointegration; calcium phosphate coating